Contracting colonialism and the long 1970s symposium - Rafael, Vicente L. (Philippine Studies: Historical and Ethnographic Viewpoints, 2013)
How is it that a book published over twenty-five years ago dealing with a distant historical moment, consisting of a series of close readings of equally obscure texts that few scholars of even the same period bother to read and informed by a style of thinking largely foreign to nationalist ideas, continues to be read and referenced not only in the Philippines but in other parts of the world? This article seeks to answer this question by placing the making of Contracting Colonialism within the context of the long 1970s in both the Philippines and the United States.